Optimization design of structure invulnerability in space information network - Fei-hong DONG; Jing LV; Xiang-wu GONG; Chao LI (Tongxin xuebao)
Combined with the space information network architecture design requirements,a novel optimization design technology was proposed,which could achieve strongly network structure invulnerability.The natural connectivity was analyzed and selected as the invulnerability measure.In addition,a modified artificial immune algorithm was proposed based on the natural connectivity and the immune review.Results show that the proposed method improves the network invulnerability performance and provides a better robustness compared with typical space information systems in link failure mode and node failure mode.